O sertão romântico: leitura de O Sertanejo, de Alencar, e de Inocência, de Taunay - Nunes, Monica Cristina Nascimento (2014)
This work, The romantic hinterland: reading O sertanejo, from Alencar, and Inocência, from Taunay, investigates the backwoods theme in literary representation, particularly, in the two works in question. The first contacts between Indians and colonists were responsible for the formation of a miscegenation that would be represented in the literary imagination, and would be highlighted by the writers of the nineteenth century. In this configuration, the Indian component was followed by a result of miscegenation with the Portuguese colonizers, the backcountry man. Thus, we divide the work into two parts. At first, we studied the Brazil-backcountry from José de Alencar, through the representations of the earth, the backcountry man and woman. Second, we study the Brazil-backcountry from Taunay, with his backcountry man and woman. To do so, this study was supported by the dialectical criticism of Antonio Candido and his disciples, and by the appliance of the understanding concepts of the backcountry universe disseminated by the sociologist and anthropologist Darcy Ribeiro, as well as, by Sergio Buarque de Holanda . Thus, literary, historical and sociological elements were brought together to an intertextual analysis of the various constituents of the nuances present in the backcountry universe in the researched literary corpus, O sertanejo and Inocência.